Bicaudal D1 impairs autophagosome maturation in chronic obstructive pulmonary disease. Issue 11 (29th October 2019) - Mercado, Nicolas; Colley, Thomas; Baker, Jonathan R.; Vuppussetty, Chaitanya; Kono, Yuta; Clarke, Colin; Tooze, Sharon; Johansen, Terje; Barnes, Peter J.
Abstract: Bicaudal D1 (BICD1), an adaptor for the dynein‐dynactin motor complex, has been identified as a susceptibility gene in chronic obstructive pulmonary disease (COPD). Autophagy, an essential cellular homeostasis process, is defective in COPD, in which oxidative stress‐induced misfolded proteins accumulate into toxic aggregates dependent on the accumulation of the autophagic cargo receptor p62. Defective autophagy can be caused by mutations in the dynein and dynactin motor complex suggesting a possible link between BICD1 and defective autophagy in COPD. BICD1 levels were measured in peripheral lung tissue from COPD patients together with markers of autophagy and found to be increased in COPD together with autophagosomes, p62 and p62 oligomers. In vitro exposure of bronchial epithelial cells to cigarette smoke extracts (CSEs) revealed that high concentrations of CSE induced defective autophagosome maturation with accumulation of BICD1, p62 and ubiquitin‐associated p62 oligomers. This was confirmed in vivo using CS‐exposed mice. Furthermore, we identified that formation of CS‐induced p62 oligomers required an interaction with Keap1. Overexpression and ablation of BICD1 confirmed that increased BICD1 negatively regulates autophagosome maturation inducing accumulation of p62 and p62 oligomers and that it can be reversed by cardiac glycosides. We conclude that defective autophagosome maturation in COPD is caused by oxidative stress‐mediated BICD1 accumulation.